ASGE Bariatric Endoscopy Task Force systematic review and meta-analysis assessing the ASGE PIVI thresholds for adopting endoscopic bariatric therapies - Abu Dayyeh, Barham K.; Kumar, Nitin; Edmundowicz, Steven A.; Jonnalagadda, Sreenivasa; Larsen, Michael; Sullivan, Shelby; Thompson, Christopher C.; Banerjee, Subhas (Gastrointestinal endoscopy, 2015)
The increasing global burden of obesity and its associated comorbidities has created an urgent need for additional treatment options to fight this pandemic. Endoscopic bariatric therapies (EBTs) provide an effective and minimally invasive treatment approach to obesity that would increase treatment options beyond surgery, medications, and lifestyle measures. This systematic review and meta-analysis were performed by the American Society for Gastrointestinal Endoscopy (ASGE) Bariatric Endoscopy Task Force comprising experts in the subject area and the ASGE Technology Committee Chair to specifically assess whether acceptable performance thresholds outlined by an ASGE Preservation and Incorporation of Valuable endoscopic Innovations (PIVI) document for clinical adoption of available EBTs have been met. After conducting a comprehensive search of several English-language databases, we performed direct meta-analyses by using random-effects models to assess whether the Orbera intragastric balloon (IGB) (Apollo Endosurgery, Austin, Tex) and the EndoBarrier duodenal-jejunal bypass sleeve (DJBS) (GI Dynamics, Lexington, Mass) have met the PIVI thresholds. The meta-analyses results indicate that the Orbera IGB meets the PIVI thresholds for both primary and nonprimary bridge obesity therapy. Based on a meta-analysis of 17 studies including 1683 patients, the percentage of excess weight loss (%EWL) with the Orbera IGB at 12 months was 25.44% (95% confidence interval [CI], 21.47%-29.41%) (random model) with a mean difference in %EWL over controls of 26.9% (95% CI, 15.66%-38.24%; P ≤ .01) in 3 randomized, controlled trials. Furthermore, the pooled percentage of total body weight loss (% TBWL) after Orbera IGB implantation was 12.3% (95% CI, 7.9%–16.73%), 13.16% (95% CI, 12.37%–13.95%), and 11.27% (95% CI, 8.17%–14.36%) at 3, 6, and 12 months after implantation, respectively, thus exceeding the PIVI threshold of 5% TBWL for nonprimary (bridge) obesity therapy. With the data available, the DJBS liner does appear to meet the %EWL PIVI threshold at 12 months, resulting in 35% EWL (95% CI, 24%-46%) but does not meet the 15% EWL over control required by the PIVI. We await review of the pivotal trial data on the efficacy and safety of this device. Data are insufficient to evaluate PIVI thresholds for any other EBT at this time. Both evaluated EBTs had ≤5% incidence of serious adverse events as set by the PIVI document to indicate acceptable safety profiles. Our task force consequently recognizes the Orbera IGB for meeting the PIVI criteria for the management of obesity. As additional data from the other EBTs become available, we will update our recommendations accordingly.